4(2x+8)=16+3(x-6)

Simple and best practice solution for 4(2x+8)=16+3(x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x+8)=16+3(x-6) equation:



4(2x+8)=16+3(x-6)
We move all terms to the left:
4(2x+8)-(16+3(x-6))=0
We multiply parentheses
8x-(16+3(x-6))+32=0
We calculate terms in parentheses: -(16+3(x-6)), so:
16+3(x-6)
determiningTheFunctionDomain 3(x-6)+16
We multiply parentheses
3x-18+16
We add all the numbers together, and all the variables
3x-2
Back to the equation:
-(3x-2)
We get rid of parentheses
8x-3x+2+32=0
We add all the numbers together, and all the variables
5x+34=0
We move all terms containing x to the left, all other terms to the right
5x=-34
x=-34/5
x=-6+4/5

See similar equations:

| 12(x+35)=516 | | 10(0.4+0.5)=4y | | n^2-64/121=0 | | 5x-2(x+10)=44 | | 780-x=6 | | Y^2-6y=72 | | 5b2+15b=0 | | 92=6x+7(-3-4) | | 3xxx=486 | | s/8=96 | | 12(m+4/9)-16=118 | | -16x^2+5x+40=29 | | 3/4m=-41/2 | | 3/5c=13 | | 3.25m=-19.5 | | 3x+2=11;=4 | | 1/128=25^x+1 | | 3/5x=12/10 | | 7/8z=6 | | 3m=36-6 | | 7*9-7=x | | 12x-3x+84=12x+36 | | x.1.5=9/4.5 | | 38=8+6j | | C+3c=2 | | 0=-16t^2+80t-29 | | 0=-16t^2-80t-29 | | -3(d-4)=-2d-2(8=+4d) | | 5x−2=−8 | | y/7+13=21 | | 4(c+3c)=2 | | x3+x6=11 |

Equations solver categories